EXPLORING EFL LEARNERS’ EXPERIENCE TOWARD THE UTILIZATION OF DUOLINGO FOR VOCABULARY MASTERY - Anggraeni, Novita Dhea; Degeng, Putu Dian Danayanti (University of Kuningan, 2024)
Teaching and learning vocabulary is somewhat troublesome for EFL learners, especially Indonesian learners. At this point, the majority of vocabulary teaching in the classroom still uses a traditional approach, meanwhile the involvement of ICT in educational environments is thought to promote the advancement of learners' expertise and skills. This research aimed to examine the effectiveness of using media based-technology especially Duolingo to increase learners’ English vocabulary mastery. In this research, the researcher used a qualitative method, a case study as research design. This research was conducted in one of the private schools in Malang, East Java with 31 students as the participants. The results of this research showed that the majority of learners believe that learning a foreign language, especially its vocabulary, through Duolingo is straightforward because the vocabulary material is relevant to everyday life. This is supported by several findings regarding Duolingo facilities, which includes easy access, user-friendly, and engaging vocabulary games and activities that enable learners to feel more motivated and enthusiastic in learning English. This study implies that Duolingo is an effective tool for supporting learners in learning foreign languages, especially mastering new English vocabulary.